″The issue of the efficiency of teaching modern foreign languages to students of non-linguistic higher education institutions″ - Andriienko, V. (Problems of Engineer-Pedagogical Education, 2018)
The importance of the issue selected for the research is related to the process of teaching English to students of non-linguistic specialties. Nowadays it is very important for specialists in different spheres to know the English language for their work as in today's world English is the global international language. The aim of the investigation is to analyze the factors which condition successful acquisition of the English language by students of non-linguistic specialties. The paper describes the main factors which influence teaching English, such as motivation, ability to work independently, age and psychological characteristics of students, students' creative abilities, and efficiency of teaching methods. The article offers a suggestion as to how to increase students’ motivation for studying English and analyzes the effectiveness of students’ independent work. There is also a suggestion for using an individual-differentiated approach to students, taking into account their personal characteristics, the importance of using visual aids and design techniques.